Rhabdophane group minerals in the uranium ore district of northern Bohemia (Czech Republic) - Scharmova,M.; Scharm,B. (Journal of the Czech Geological Society, 1994)
Four mineral species of the rhabdophane group, namely: ningyoite, brockite, rhabdophane-(Ce), and rhabdophane-(Nd) are found in the sandstone type uranium ore district in the Bohemian Cretaceous Basin. Electron microanalyses indicate the existence of a continuous isomorphic series between ningyoite and brockite which is manifested by the unlimited mutual substitution of U and Th. However, there are pronounced differences in the habit and dimensions of the Th-bearing members on the one hand and the Th-free member (“pure” ningyoite) on the other. Rhabdophanes are characterized by a wide range of REE proportions. The occurrence of rhabdophane-(Nd), unusual La-free rhabdophane-(Ce) together with the earlier discovered phosphates, arsenates, and fluorocarbonates with Nd- and La-dominated composition indicate a distinctive fractionation of rare earth elements during exogenic processes.